My contemporaries by Stanisław Przybyszewski – autobiography of Polish misanthrope - Zaród, Magdalena (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
Stanislaw Przybyszewski’s worldview was shaped in the age of cultural change, which was marked by a profound identity crisis of individuals related to the re-evaluation of the market of cultural values: traditionally understood maternity, paternity, male and female roles. Misoginism was the result of this moment of history, when everything that was so certain, became unpredictable, and the patriarchal culture had to give way to a new, expansive, struggling for its rights matriarchal culture. My contemporaries by S. Przybyszewski, is a testimony to the crisis of culture, in which the subject, despite his sincerest wishes, can no longer identify with the identity patterns it offers (Dybel, 2000: 59). The consequence of such an internal disintegration is suffering, the longing for something undefined, the desperate quest for one’s own self, and, finally, the conscious creation of one’s own legend, which is undertaken by S. Przybyszewski in My Contemporaries.